PENGARUH KOMBINASI PEMBERIAN PAKAN PELET DAN PAKAN NABATI YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN GURAMI (Osphronemus gouramy) - Adiningsih, Baiq Endang; Diniarti, Nanda; Abidin, Zaenal (Journal of Fish Nutrition, 2023)
Gouramy (Osphronemus gouramy) is one of the freshwater fishery commodities that are in great demand by the public, both by consumers and cultivators. Consumers like gouramy because it tastes delicious and tasty, while cultivators like gourami because it has a higher selling price compared to other freshwater fishery commodities. Feed is an important component in fish farming activities. Feed is a source of material and energy to support the growth and survival of fish, on the other hand feed is also the largest component of 50-70% of production costs. The purpose of this study was to determine the effect of feeding a combination of pellets and vegetable feed on the growth and survival of gouramy and to see the best type of vegetable feed. The results of the research were the results of the test parameters measured during the study, namely absolute weight growth, specific weight growth, absolute length growth, specific length growth, feed conversion ratio (FCR), feed efficiency level (EPP), and survival rate (SR). As well as water quality data including the degree of acidity (pH), temperature, dissolved oxygen (DO), ammonia and alkalinity. The results of parameter measurements showed that the P4 treatment showed the best results for each parameter that had been observed. The effect of giving a combination of pellet feed and vegetable feed on gourami (Osphronemus gouremy) seed cultivation gave insignificant results on absolute weight growth, specific weight growth, absolute length growth, specific length growth, feed conversion ratio, feed efficiency level, and survival rate live gourami. Treatment 3 (a mixture of pellets and papaya leaves) gave the best results compared to other treatments.